1232 Innovative online newborn care potential benefits and challenges of online lactation consultation services with paediatrician support: a cross-sectional survey study. (17th August 2022) - Hamid, Muhammad; Kumar, Anubha; Gunaseelan, Luxhman; Arulchelvan, Atchaya; Sinha, Abhinav; Subhan, Muzhda; Subhan, Sarah; Kapoor, Suruchi; Salim, Asim
Abstract : Aims: Telelactation, a virtual lactation support platform, is a convenient and effective way of providing virtual breastfeeding support services and communicating proper breastfeeding techniques to new mothers to address any breastfeeding challenges and boost overall maternal breastfeeding confidence all from the comfort of their homes. This Ontario Health Insurance Plan (OHIP) covered service benefits more to mothers in remote areas where in-person LC service is not easily accessible. The objective of this cross-sectional survey study is to explore the feasibility, potential benefits, challenges, and level of patient satisfaction in virtual lactation consultation services available in Ontario, Canada. Methods: Patient satisfaction was assessed using a structured online survey as a part of a cross-sectional observational study that asked questions relevant to several independent demographic variables as well as specific Likert type scale questions to gauge patient satisfaction with virtual lactation consultation. Results: Data from 177 survey responses (n=177) was analyzed, of which the study revealed that 86.44% (153/177) were satisfied with the virtual lactation services they received. Patient satisfaction was found to be higher in the first-time mothers with high school or undergraduate education between the age group of 26-35 years living in the Greater Toronto Area (GTA). In terms of connectivity, participants from the GTA had a better experience overall compared to those living outside the GTA. Conclusion: OHIP covered telelactation is an innovative and feasible health care delivery platform for providing remote professional breastfeeding support to mothers of all socio-economic strata with great potential to further improve both patient experience and efficiency in patient care.